Comparative study of Smartphone Addiction among Arts and Medical College Students of Port Blair - Shivani Rao; Ajay Raj Sethuraman; Pandurang Thatkar (Medsci Publications, 2019)
Background: Smartphones have become an integral part of every- one's life. Smartphones can be a boon if used in correct way but if misused it can result in smartphone addiction. The objectives of the study were to compare smartphone usage among undergradu- ate medical college and arts college students of Port Blair and also to evaluate the demographic profile of smartphone users. Materials and Methods: A cross sectional study was conducted among 149 arts students and 192 medical students. SAS scale has been used to assess the smartphone addiction. The participants were divided into low smart phone user group and a high smart- phone user group. Results: Among the Arts group out of the total 149 students, 35 students (23.50%) were low smartphone users and 114 (76.50%) were high smart phone users. In the medical group 28 students (14.58%) were low smart phone users and 164 (85.42%) were high smartphone users. High smart phone usage was seen among fe- male students in both arts (79.82%) and medical colleges (67.07%) Conclusion: Proportion of Smartphone addiction was high among medical college students.